Tourism firms’ attitudes and willingness to contribute to payments for ecosystem services in tourism - Konu, Henna; Leino, Pinja; Tyrväinen, Liisa (Taylor & Francis, 2025)
The purpose of this study is to contribute to the discussions of the role of tourism firms in maintaining important natural environments and cultural ecosystem services of a tourism destination. More precisely, this study explores the tourism firms’ attitudes and willingness to participate in safeguarding and maintaining cultural ecosystem services in a destination through a tourism-related local payments model, Landscape and Recreation Value Trade (LRVT), developed in the Ruka-Kuusamo area in Finland. Five main themes illustrating tourism firms’ attitudes towards LRVT and willingness to contribute to it were identified: benefits, concerns and challenges, implementation, characteristics of a firm, and need for raising awareness. Based on the findings many of the expressed benefits and challenges of LRVT originate from and are connected to evaluating the impacts on the competitiveness of the firm and the competitive advantages for the destination. The study brings insight into the planning, design, and implementation of voluntary tourism-related payment schemes for ecosystem services, and discusses their potential to enhance ecological conservation, support the local economy, and serve as an incentive for private firms to act in a more sustainable manner.
Keywords: luontomatkailu; kulttuuriset ekosysteemipalvelut; ekosysteemipalvelumaksut; maisema-arvokauppa; Payments for ecosystem services; Landscape and Recreation Value Trade; tourism firms; willingness to contribute; nature-based tourism; cultural ecosystem services